2015
DOI: 10.1111/clr.12567
|View full text |Cite
|
Sign up to set email alerts
|

Digital versus conventional implant impressions for edentulous patients: accuracy outcomes

Abstract: Digital implant impressions are as accurate as conventional implant impressions. The splinted, implant-level impression technique is more accurate than the non-splinted one for completely edentulous patients, whereas there was no difference in the accuracy at the abutment level. The implant angulation up to 15° did not affect the accuracy of implant impressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
284
3
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(313 citation statements)
references
References 32 publications
(51 reference statements)
13
284
3
13
Order By: Relevance
“…In particular, the former internal gap study includes Seelbach et al's studyon the single crown and Schaefer et al's on the partial crown while the latter image superposition study includes Nedelcu et al's study on simplified and standardized scan body, Ender et al's on full arch, and Patzelt et al's on edentulous jaws 235678910. Papaspyridakos and Wismeijer reported the investigation on the accuracy of digital implant impressions with IOS 111213. In the study on the measurement of the gap of crowns, there is a limitation in determining the performance of the scanner itself due to the uncontrollable factors occurring in the fabrication of crowns while the image superposition study suggests neither the relationship with the actual crown nor the data for the specific important sites such as margins since this is a mere comparison of images.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the former internal gap study includes Seelbach et al's studyon the single crown and Schaefer et al's on the partial crown while the latter image superposition study includes Nedelcu et al's study on simplified and standardized scan body, Ender et al's on full arch, and Patzelt et al's on edentulous jaws 235678910. Papaspyridakos and Wismeijer reported the investigation on the accuracy of digital implant impressions with IOS 111213. In the study on the measurement of the gap of crowns, there is a limitation in determining the performance of the scanner itself due to the uncontrollable factors occurring in the fabrication of crowns while the image superposition study suggests neither the relationship with the actual crown nor the data for the specific important sites such as margins since this is a mere comparison of images.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of implant angulation on the accuracy of implants casts fabricated with different methods remains an area for further investigation. Several studies reported no significant differences in the accuracy of implant casts for implant angulation up to 15° . Literature is not yet conclusive, but the currently available evidence shows that more than 20° angulation may be associated with higher 3D deviations .…”
Section: Discussionmentioning
confidence: 77%
“…An operator blinded to the type of casts performed all digital scanning procedures. In order to capture the 3D orientation of the implants in each test cast and their 3D deviations, the Standard Tessellation Language (STL) volumes from the three test groups were registered using a surface based registration algorithm . The cumulative 3D deviations between the control STL file and the 45 test STL files were calculated with superimposition software (Geomagic).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former, however, is affected by intrinsic errors and variability due to the use of conventional impression materials and their development in plaster. Intraoral scans can greatly facilitate and standardise dental impression taking also in more difficult cases such as full-arch scans [17] and even in the case of edentulous arches [18], although further clinical studies would need to be conducted for these types of clinical cases. It should be noted, however, that there is some variability with regard to the precision and accuracy of various intraoral scanning systems [19].…”
Section: Discussionmentioning
confidence: 99%